Telemedicine Guidelines in South East Asia—A Scoping Review - Intan Sabrina, Mohamad; Defi, Irma Ruslina (Frontiers in Neurology, 2021)
Background: Telemedicine is a useful tool to deliver healthcare to communities in low to high income countries, especially in the Covid-19 pandemic era. Guidelines on telemedicine would assist healthcare providers to deliver healthcare services based on local circumstances. Objective: To explore and compare guidelines on telehealth and telemedicine in South East Asian (SEA) countries. Methods: Electronic databases such as Google, PubMed and Cochrane reviews were searched for articles using keywords such as ‘telemedicine’ OR ‘telehealth’ OR ‘eHealth’ OR ‘telemedis’ AND ‘guidelines’ AND ‘South East Asia’ OR ‘Malaysia’ OR ‘Singapore’ OR ‘Indonesia’ OR ‘Thailand’ OR ‘Vietnam’ published up to 2020. Inclusion criteria were full articles and grey materials (i.e. policy statements, advisories, blueprints, executive summaries and circulars) related to telemedicine guidelines. No language restrictions were imposed. Only the first 100 Google searches were included for eligibility based on its relevance to telemedicine guidelines. Exclusion criteria were abstracts, duplicate publications, blogs, news articles, promotional brochures, conference proceedings and telemedicine projects unrelated to telemedicine guidelines. Results: A total of 62,300 articles were identified through the search engines (Google 62,203, PubMed 77, Cochrane 20) and six articles from additional sources. Sixty-eight full text articles fulfilled the inclusion criteria, but only 24 articles contained some form of guidelines on telemedicine: Indonesia (nine), Malaysia (seven), Singapore (five), Thailand (two) and Vietnam (one). There were six laws, six advisory guidelines, five policy statements and two circulars (regulations) issued by either the Ministry of Communication and Multimedia, Ministry of Health or Medical Councils from the respective countries. Issues addressed were clinical governance, ethics and legal issues and technical aspects of telemedicine. The National Telemedicine Guidelines (NTG) from SIngapore contained the most domains compared with other guidelines from South East Asia. Conclusions: Although there can be no ‘one-size-fits-all’ telemedicine guideline, there should be a comprehensive and universal telemedicine guideline for any country to adapt based on local context. Details on patient-identification, data ownership, back-up and disposal; transregional cyber security laws and ways to overcome the limitations of telemedicine compared with face-to-face consultations should be outlined clearly to ensure uniformity of telemedicine service and patient safety.